STRENGTHENING HEALTH CADRES THROUGH STRUCTURED TRAINING FOR COMMUNITY-BASED OBESITY SCREENING - Maharani, Citra; Puspasari, Anggelia; Syauqy, Ahmad; Fitri, Amelia Dwi; Shafira, Nyimas Natasha Ayu; Perkasa, Tengku Arief Buana; Hasmita, Debby (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Obesity is a major risk factors for non-communicable diseases, and its prevalence continues to increase in Indonesia. Community Health Centers, as primary healthcare providers, play a crucial role in obesity prevention through the empowerment of local health cadres. This community service aimed to enhance cadres’ knowledge and skills in early obesity detection. The program was implemented through a structured training consisting of material delivery and hands-on anthropometric measurement sessions, followed by field visits to Posyandu to evaluate cadres’ practical skills in performing anthropometric assessments. A total of 15 Posyandu cadres from the working area of Tahtul Yaman Community Health Center participated in this activity. The results showed a significant increase in knowledge, with median scores rising from 90 (range 50–100) in the pre-test to 100 (range 80–100) in the post-test (p = 0.007). The proportion of cadres achieving the passing score also increased from 53.3% to 100% (p = 0.006). Field observations indicated that most cadres were able to perform anthropometric examinations independently and in accordance with standard procedures. These findings suggest that structured training combined with practical field reinforcement may contribute to improving cadres’ competencies, thereby supporting their role in sustainable, community-based obesity prevention efforts. Keywords: Obesity screening; Health cadres; Anthropometry; Community health center.